Rancang Bangun Sistem Kontrol Watermeter PDAM Berbasis IoT - Mukhsin Mukhsin; Muh Pauzan; Nuhasanah (Computer Science Research and Its Development Journal, 2022)
The process of checking or monitoring (control system) of water use to each customer every month which has been carried out by the Officers of the Regional Drinking Water Company (PDAM) in its implementation still uses a manual system. In the implementation of monitoring, there are often errors in recording water use, namely different calculations on the same use (Human Error). This study aims to monitor water usage digitally using an IoT (Internet of Things) based watermeter. This study uses the Root Mean Square Error (RMSE) method as a model selection tool based on the error of the estimation results. The variable used is a 1 liter measuring cup where the glass will be measured by the value read on the watermeter. The test uses a national standard calibration with a value of 6,5, with a total of 30 tests. The results of the study were carried out on 10 experiments with samples of 0,005 m3, 0,01 m3, and 0,015 m3, respectively. The results of the research on the accuracy value owned on the sample of 0,015 m3 are said to be accurate because based on the calculation scale of the RMS theory, the smaller the accuracy value, the more accurate the value issued on the watermeter tool.